Kinetic simulation of low pressure RF discharge in nonuniform axisymmetric magnetic field - Olshansky, V.V. (Вопросы атомной науки и техники, 2012)
An implicit 2D3V PIC/MCC code has been developed for the kinetic simulation of low pressure RF discharges. The code uses coupled particle-in-cell method (PIC) for calculation collisionless dynamic of the plasma particles and Monte-Carlo method (MCC) for taking in account the particle collisions. For the computation time reduction a number of physical and numerical methods of speeding up the code were introduced, such as the implicit schemes of the particles motion and fields computation, the electron sub-cycling and so on. The developed code is applied to the plasma dynamic investigation in capacitively coupled plasma RF discharge enhanced by the external magnetic field which is used in the neutral loop discharges (NLD). Для кинетического моделирования ВЧ-разрядов низкого давления разработан неявный 2D3V PIC/MCC код. Код использует метод «частица в ячейке» (PIC) для расчета бесстолкновительной динамики частиц плазмы и метод «Монте-Карло» (MCC) для учета парных столкновений частиц. Для сокращения компьютер- ного времени в коде применяются различные численные и физические методы ускорения расчета, такие как неявный метод расчета движения частиц и полей, электронные подциклы и другие методы. Разработанный код применяется для исследования динамики плазмы в ёмкостном плазменном ВЧ-разряде, усиленном внешним магнитным полем, используемом в разрядах с нейтральным контуром (NLD). Для кінетичного моделювання ВЧ-розрядів низького тиску розроблено неявний 2D3V PIC/MCC код. Код використовує метод «частинка в клітинці» (PIC) для розрахунку динаміки частинок плазми без зіткнень і метод «Монте-Карло» (MCC) для врахування парних зіткнень частинок. Для скорочення комп’ютерного часу в коді застосовано різні числові та фізичні методи прискорення розрахунку, такі як неявний метод обчислення руху частинок і полів, електронні підцикли та інші методи. Розроблений код застосовується для дослідження динаміки плазми в ємнісному плазмовому ВЧ-розряді, підсиленому зовнішнім магнітним полем, що використовується в розрядах з нейтральним контуром (NLD).